Nanoscale surface conductivity analysis of plasma sputtered carbon thin films. Issue 117 (11th November 2015) - Javid, Amjed; Kumar, Manish; Han, Jeon Geon
Abstract : The present work demonstrates the phenomenon of nanoscale surface conductivity variation in various plasma conditions of sputtering induced carbon thin films. Abstract : Understanding of surface conductivity at the nanoscale is very important for surface activities e.g. bio-activity and electronic transportations. In this work, the co-relation of surface properties to surface conductivity has been investigated in carbon films prepared by plasma sputtering. A Field Emission Scanning Electron Microscopy (FE-SEM) study provided evidence of film growth in the form of the nano-domains (NDs). Conductive atomic force microscopy (C-AFM) was used to explore the influence of growth conditions on the local current flow in carbon thin films through the induced current variation across the NDs. It is found that the growth regime of the NDs has a close relation to the power density and the working pressure. The flow of current across the internal area of the ND surface is lower than the boundaries due to the difference of conjugation in sp 2 hybridized carbon atoms. The mean current flow through the films as measured by C-AFM is in accordance with the resistivity of the films observed by the van der Pauw method.